Role of Biomarkers in Medicine - Wang, Mu; Witzmann, Frank A. (IntechOpen, 2016)
The use of biomarkers in basic and clinical research has become routine in many areas of medicine. They are accepted as molecular signatures that have been well characterized and repeatedly shown to be capable of predicting relevant disease states or clinical outcomes. In Role of Biomarkers in Medicine, expert researchers in their individual field have reviewed many biomarkers or potential biomarkers in various types of diseases. The topics address numerous aspects of medicine, demonstrating the current conceptual status of biomarkers as clinical tools and as surrogate endpoints in clinical research. This book highlights the current state of biomarkers and will aid scientists and clinicians to develop better and more specific biomarkers for disease management.